Liver fibrosis score, physical frailty, and the risk of dementia in older adults: The Italian Longitudinal Study on Aging. Issue 1 (24th August 2020) - Solfrizzi, Vincenzo; Scafato, Emanuele; Custodero, Carlo; Loparco, Francesca; Ciavarella, Alessandro; Panza, Francesco; Seripa, Davide; Imbimbo, Bruno Pietro; Lozupone, Madia; Napoli, Nicola; Piazzolla, Giuseppina; Galluzzo, Lucia; et al.
Abstract: Introduction: Liver fibrosis increases progressively with aging and has been associated with poorer cognitive performance in middle‐aged and older adults. We investigated the relationships between a non‐invasive score for advanced liver fibrosis (non‐alcoholic fatty liver disease [NAFLD] fibrosis score [NFS]) and dementia risk. We also assessed physical frailty, a common geriatric condition which is associated to dementia. We tested the joint effects of physical frailty and fibrosis on dementia incidence. Methods: A total of 1061 older adults (65 to 84 years), from the Italian Longitudinal Study on Aging, were prospectively evaluated for the risk of dementia in a period between 1992 and 2001. Liver fibrosis was defined according to the NFS. Physical frailty was assessed according to the Fried's criteria. Cox proportional hazards models were used to estimate the short‐ and long‐term risk of overall dementia, associated to the NFS, testing the effect modifier of physical frailty status. Results: Older adults with only high NFS (F3‐F4) did not exhibit a significant increased risk of overall dementia. Over 8 years of follow‐up, frail older adults with high NFS had an increased risk of overall dementia (hazard ratio [HR]: 4.23; 95% confidence interval [CI]: 1.22 to 14.70, P = .023). Finally, physically frail older adults with low albumin serum levels (albumin < 4.3 g/dL) and with advanced liver fibrosis (F3‐F4 NFS) compared to those with lower liver fibrosis score (F0‐F2 NFS) were more likely to have a higher risk of overall dementia in a long term‐period (HR: 16.42; 95% CI: 1.44 to 187.67, P = .024). Discussion: Advanced liver fibrosis (F3‐F4 NFS) could be a long‐term predictor for overall dementia in people with physical frailty. These findings should encourage a typical geriatric, multidisciplinary assessment which accounts also for the possible co‐presence of frail condition in older adults with chronic liver disease and liver fibrosis.